Modelagem da retração por secagem de concretos produzidos com agregados reciclados - Cabral, Antonio Eduardo Bezerra (2021)
Concerns with conservation of nonrenewable resources are propelling academic research regarding the use of recycled aggregates in concrete production. Concrete’s shrinkage is a phenomenon intimately linked to concrete loss of water, which is almost inevitable, since the majority of concrete structures is exposed to an environment where atmospheric humidity is below saturation condition. This paper presents an experimental study where concretes were produced varying water/cement ratio (from 0.4 to 0.8) and type and proportion of construction & demolition waste (concrete, cement, and red ceramic) used as coarse and fine recycled aggregates. Mathematical models correlating such variables with concrete’s shrinkage at 56 and 224 days of age were built. The results indicate that, for the age of 56 days, the data presented excessive variability, revealing only 4 of the 7 tested variables as significant. For the age of 224 days, the proposed model still presented considerable variability, however all tested variables were detected as significant. Results point out that substitution of natural aggregates by recycled aggregates increases shrinkage, being this effect stronger when substitution comprises fine aggregates. The most pronounced effect was associated to the use of recycled concrete fine aggregate. The slightest effect was observed using recycled concrete coarse aggregate.